О диалоге культур и целях образования в условиях глобальных кризисов - Иванов, Евгений Вячеславович (International Dialogues on Education Journal, 2016)
The article represents the author’s reflections about contemporary challenges humankind during global crises and their dialectical interrelationship with cultures’ interactions and modern educational objectives. Within the context of European multicultural crises the following idea is advanced and proved: «What is good for one culture is not always acceptable, and occasionally harmful, for the other one». In the context of global crises the following problem of humankind that compels us to rethink some current life values and priorities, is advanced: «How to move on in order to survive?». The difference between communist and capitalist ways of development consists of political and economic mechanisms of achievement of global purpose: the accomplishment of the constantly growing urge of people – ‘to have everything’. There is the question: «Is this the right purpose?». In the conclusion of the article it is mentioned that the global strategic goal of modern education is humankind’s deliverance from consumer psychology. People need to recognize and give priority to inner values and pay careful attention to the moral aspect of human existence.